Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(y^2+4^x+2y-2^{x+1}+2=0\)
\(\Leftrightarrow\left(y+1\right)^2+\left(2^x-1\right)^2=0\) ( * )
Do \(\left(y+1\right)^2\ge0\forall y;\left(2^x-1\right)^2\ge0\forall x\Rightarrow\left(y+1\right)^2+\left(2^x-1\right)^2\ge0\forall x;y\)
Từ ( * ) \(\Rightarrow\left\{{}\begin{matrix}\left(y+1\right)^2=0\\\left(2^x-1\right)^2=0\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}y+1=0\\2^x-1=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}y=-1\\x=0\end{matrix}\right.\)
Vậy ....
\(y^2+2y+1+\left(2^x\right)^2-2.2^x+1=0\)
\(\Leftrightarrow\left(y+1\right)^2+\left(2^x-1\right)=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}y+1=0\\2^x-1=0\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}y=-1\\x=0\end{matrix}\right.\)
Lời giải:
$y^2+4^x+2y-2^{x+1}+2=0$
$\Leftrightarrow (y^2+2y+1)+(4^x-2^{x+1}+1)=0$
$\Leftrightarrow (y^2+2y+1)+[(2^x)^2-2.2^x+1]=0$
$\Leftrightarrow (y+1)^2+(2^x-1)^2=0$
Ta thấy:
$(y+1)^2\geq 0; (2^x-1)^2\geq 0$ với mọi $x,y$
Do đó để tổng của chúng bằng $0$ thì:
$(y+1)^2=(2^x-1)^2=0$
$\Leftrightarrow y=-1; x=0$